Farm economic sustainability – financial ratio analysis - Wilczyński, Artur (Trwałość ekonomiczna gospodarstw – analiza wskaźników finansowych, 2020)
Sustainable development is widely regarded as one of the pillars of building policies, strategies and business models. This assumption also applies to creation of specific practices related to running farm business. The key issue is how to measure agriculture sustainability. The article assesses the economic area of sustainable agriculture using the economic sustainability index, constructed on the basis of sixteen financial indicators. The source of data was the FADN, from which data on the economic situation of dairy farms (type 45). As a result of the research, the relationship between the economic size and the value of the economic sustainability index were determined. The research area covered five countries that are the largest dairy producers in European Union. In this case, high discrepancies in the level of economic sustainability index between farms were noted
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 2, s. 120-131
Keywords: sustainable agriculture; dairy farms; efficiency; profitability; rolnictwo zrównoważone; gospodarstwa mleczne; efektywność; dochodowość